Gambaran Kadar Hemoglobin Pre dan Post Melahirkan Caesar - Eko Puji Rahayu (Poltekkes Kemenkes Semarang, 2019)
Cesarean delivery without any indication of an increase should the procedure be safer but there is still an increased risk for pregnant women who have a cesarean birth, which is bleeding. To find out the description of hemoglobin levels pre and post cesarean delivery at the Mother and Child Hospital Dian Pertiwi Karanganyar Regency. This research is secondary data research taken from medical record installations at Dian Pertiwi Mother and Child Hospital in Karanganyar Regency. Of 82 samples of pregnant women who gave birth by cesarean at the Mother and Child Hospital Dian Pertiwi Karanganyar 44 (60%) with normal hemoglobin levels above 12 gr/dl pre-cesarean section and 38 (40%) with hemoglobin levels 11 gr/dl post cesarean section. Samples of pregnant women who gave birth by cesarean and there was no history of anemia before cesarean section, after cesarean section decreased hemoglobin levels 2.1 gr/dl. The decrease in hemoglobin level is also supported by the management carried out by a very experienced operator, according to the procedure that makes a decrease in hemoglobin levels is not much.